Currículo na educação infantil: um olhar reflexivo para re(pensar) o desenvolvimento da oralidade em crianças de quatro e cinco anos de idade - Leite, Márcia Soares de Arruda (2014)
In this paper we present a project of a pedagogical intervention which is a conclusion of a research for a Master’s Degree in Linguistics and Teaching of UFPB. Its subject is: curriculum in child education: a reflective look for (re)thinking the development of orality in children from four to five years old. It was developed in one of the main full-time child education institutes of João Pessoa city, which works only with children in the target age of the research. The research started in February and ended in September 2013. In its structure we specify what was developed in the school with twelve teachers (including the researcher) by means of a collaborative project essential to guide and encourage all moments experienced during its execution. The objective of the project was to arrange studies and reflections about curriculum, specifically Child Education curriculum, focusing on orality, and to reflect and make the participants aware of the importance of experiencing orality daily in school, and sharing the knowledge in pedagogy workshops. We used a qualitative research approach in a collaborative way, highlighting data we analyzed in a constant dialogue with the theory, realizing they show ways for (re)constructing the Child Education curriculum, revealing the importance of continuous formation for our professional and personal growth, announcing possibilities of implementing teacher’s practices, associating them to the joy and enchant of being in a Child Education Institute.